Racionální lécba nekrotizující externí otitidy - Hlozek, J; Slapák, I; Kucera, P (Casopis lekaru ceskych, 1989)
Advances in the diagnosis and treatment of necrotizing external otitis (NEO) during the past 20 years improved substantially the prognosis of this disease. The use of hyperbaric oxygen therapy greatly potentiates the effect of newly developed highly effective antibiotics. Radioisotope examination of the petrous bones facilitates the diagnosis and indicates the time to terminate treatment. Medicamentous treatment is preferable to surgical treatment, which is reserved for exceptional very advanced cases of the disease. As NEO has been known for 30 years and the means to control it have been improved, it is no longer "malignant" for the majority of patients where the disease is diagnosed in time and treated adequately.
Keywords: Humans; Necrosis; nekróza; Otitis Externa; otitis externa; senioři; mužské pohlaví; Aged; Male; pseudomonádové infekce; lidé; Pseudomonas Infections